Climate-Smart Agriculture in Benin - Food and Agriculture Organization of the United Nations; CGIAR Research Program on Climate Change, Agriculture and Food Security; International Crops Research Institute for the Semi-Arid Tropics (Food and Agriculture Organization of the United Nations, 2018)
This Benin country CSA profile provides a snapshot of a developing baseline created to initiate discussion, both within countries and globally, about entry points for investing in CSA at scale.